“That was really a productive segment, wasn’t it?” Nonverbal markers of humor in the American presidential debates of 2016 and 2020 - Tabacaru, Sabina (Frontiers in Psychology, 2025)
These past few years have marked a growing interest in multimodality, interaction and eye-gaze in the interpretation and understanding of discourse. Eye-gaze, for example, plays a central role in face-to-face interaction and stance taking because it helps discourse participants coordinate with each other. Such visual markers help the interlocutors/audience to intersubjectively connect to the same common ground on which they construe their meanings. The case of humor has also received more attention from a multimodal perspective since it follows the same patterns of meaning construction and coordination. Elements that are salient to the humorous interpretation will be emphasized using either prosodic cues or visual markers, such as facial expressions and head movements. In this paper, we explore the use of such nonverbal discourse markers with the use of humor in the American presidential debates of 2016 and 2020, analyzing their role on the humorous stance.